Profil VAK dan Asesmen Diagnostik sebagai Prediktor Motivasi Belajar Siswa Kelas IV SD Diferensiasi Kurikulum Merdeka: VAK Profile and Diagnostic Assessment as Predictors of Learning Motivation among Grade 4 Elementary Students under the Merdeka Curriculum Differentiation - Munira Munira; Rahmi Novalita; Yulia Santi (ITScience (Information Technology and Science), 2026)
The transformation of 21st-century education demands instruction that is responsive to learners' diverse characteristics. The *Kurikulum Merdeka* (Independent Curriculum) encourages the implementation of diagnostic assessments and differentiated instruction to accommodate students' diverse learning needs. However, the implementation of these approaches in primary schools still faces various challenges and has not been carried out optimally or systematically, including in the Aceh region. This study aims to analyze the relationships among learning styles, learning motivation, and cognitive diagnostic assessment results in primary school students. This quantitative study, employing a correlational design, involved 30 fourth-grade students from UPTD SD Negeri 4 Simpang Mamplam, Bireuen Regency. Research instruments included the Visual, Auditory, and Kinesthetic (VAK) learning style questionnaire, a learning motivation questionnaire, and a cognitive diagnostic test. Data were analyzed using descriptive statistics, the Kruskal–Wallis test, and Spearman correlation. The learning style profile showed a predominance of the Visual style (46.7%), followed by Auditory (30.0%) and Kinesthetic (23.3%). Students' learning motivation fell into the High and Very High categories, with an average achievement of 86.3% of the maximum score. There was a significant difference in learning motivation across learning style groups (H = 8.214; p = 0.016), with the Visual group exhibiting the highest motivation. Furthermore, significant positive correlations were found between learning style and learning motivation (r? = 0.706; p < 0.001), between cognitive diagnostic assessment and learning motivation (r? = 0.589; p = 0.001), and between learning style and diagnostic assessment results (r? = 0.418; p = 0.021). The diversity of learning styles and their link to learning motivation underscore the importance of conducting diagnostic assessments as a foundation for designing differentiated instruction that can optimally accommodate students' learning needs.